PENGUATAN PENDIDIKAN AGAMA ISLAM (PAI) SEBAGAI KURIKULUM INTI DI SEKOLAH - Syarif, Miftah (Jurnal Pendidikan Guru, 2017)
Islamic Religious Education is a complex and comprehensive education touches the whole area of education. Rahmatan Lilâalamien. Islamic Religious Education does not just take the discourse on religious knowladge course material to students, but also to guide students to behave in accordance with the values taught by religion that promotes akhlakul karimah or noble character as the basic behaviour that should be owned by the learner. The position of Isla,mic religious education among other subjects at school is as the core in the nationa education curriculum. Therefore in practice in the field should be about [roviding transparency understanding and application process, thus giving birth to attitudes and behaviors that are inclusive and positioned equivalent to other subbjects or even prioritized. For it puts the subjects os islamic religious education as a core subject in the school curriculum is a need and a necessity. This is an intelligent effort to strengthen forms of islamic religious education in the school curruculum. So, Islamic religious education covers all aspects of integrated subjects in knowladge, attitudes, behaviour, and social interaction. Islamic religious education is more oriented to the moral level of action, namely that learners do not just stop at the level of competence, but to have the will, and habit, in realizing the teachings and values of the islamic religion in everyday life.